2010
DOI: 10.1002/pola.24472
|View full text |Cite
|
Sign up to set email alerts
|

Crown‐ether and azobenzene‐containing liquid crystalline polymers: An influence of macromolecular architecture on optical properties and photo‐orientation processes

Abstract: A series of novel crown ether‐containing photochromic comb‐shaped liquid crystalline polyacrylates with different macromolecular structure of side groups were synthesized and investigated. Phase behavior, optical and photo‐optical properties of thin spin‐coated films of these polymers were studied. A special attention was paid to a comparative study of the photo‐orientation phenomena occurring in the polymer films under a polarized light action. It was shown that complex formation with the potassium ions resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The investigation of the relationship between molecular architecture of this type polymers and their photo-optical properties and phase behavior was the main scope of studies. Bobrovsky and co-workers [ 260 ] described among others the synthesis and properties of two types of polymers differing in the position of the crown ether in relation to the photoresponsive azobenzene residues (Fig. 89 ).…”
Section: Polymers Bearing Macrocycle(s) and Azo Motif(s)mentioning
confidence: 99%
“…The investigation of the relationship between molecular architecture of this type polymers and their photo-optical properties and phase behavior was the main scope of studies. Bobrovsky and co-workers [ 260 ] described among others the synthesis and properties of two types of polymers differing in the position of the crown ether in relation to the photoresponsive azobenzene residues (Fig. 89 ).…”
Section: Polymers Bearing Macrocycle(s) and Azo Motif(s)mentioning
confidence: 99%
“…Initiator Irgacure 651 was purchased from Ciba. A6Crown was synthesized according to method described previously 18. Perchlorates of barium and potassium were used as received (Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…In recent works performed in our laboratory,18, 19 the novel type of side‐chain polymers containing crown ether and azobenzene fragments in one and the same macromolecule were synthesized, and it was shown that complexation in such polymers leads to significant decrease of isotropization temperatures, change of E/Z isomerization mechanism, and, as a consequence, change of photo orientation process peculiarities. Apart from the rather complex synthesis of such systems, they are not suitable as the materials for sensors since complexation processes are characterized by slow rate because they proceed in polymeric glassy state.…”
Section: Introductionmentioning
confidence: 99%